Effect of Gibberellin (GA3) Application on the Growth Rate of Hydroponic Alfalfa (Medicago sativa L.) Fodder - Ahimsa Kandi Sariri; Sri Lestari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Feed is a major component in livestock production; however, the availability of forage is often constrained by limited land resources and seasonal fluctuations. A leguminous plant, alfalfa (Medicago sativa L.) is sometimes referred to as the